(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
The genus Rubus is in botany a group that has been totally neglected for many decades because of its complexity, of its immense variability linked to its high rate of hybridization and the very small number of national botanists interested in it. The article attempts to provide an overview of the work to be done from 3 test prospecting areas in the north of the Massif central. A local historical approach is discussed in the introduction, then elements of taxonomy and identification are discussed, and finally simple statistical data based on contemporary prospecting are exposed.